The Effects of Psychic Distance and Inter-Partner Fit on the Performance of International Joint Ventures - Ishita Batra; Sanjay Dhir (Asian Academy of Management Journal, 2019)
The impact of psychic distance stimuli and inter-partner fit on the performance of international joint ventures (IJVs) has not been adequately explored in the case of emerging economies. Another lacuna in literature is the analysis of the performance of IJVs in regard to the new normal business landscape. This study analyses the impact of psychic distances stimuli and inter-partner fit on the performance of IJVs in the context of new normal business landscape. The secondary data of 122 IJVs headquartered in India with G7 nations is empirically tested. The study indicates that out of all psychic distances, administrative and economic distances significantly affect the performance of IJVs.